2020
DOI: 10.1111/desc.13004
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dynamics between reading and math in elementary school

Abstract: Children experiencing difficulties in reading and math represents an important public health issue, as struggles with reading and math are associated with consequences regarding academic and life success, including but not limited to academic failure and lower socioeconomic status as an adult (Geary, Hoard, Nugent, & Bailey, 2012; Ritchie & Bates, 2013). Highlighting the scope of this problem, a large proportion of U.S. students struggle in reading and math. Startling enough, 20%-25% of fourth-graders fail to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 62 publications
(123 reference statements)
7
52
1
1
Order By: Relevance
“…Although the magnitude of this association was small, it was consistent over development. Erbeli et al (2020) reported similar findings in elementary children from grades 1 to 4, where annual change in math growth was (partially) accounted for by reading achievement. The reverse coupling, annual change in reading growth predicted by math achievement, was not found.…”
Section: Cross-domain Associations Between Reading and Mathematicssupporting
confidence: 58%
See 1 more Smart Citation
“…Although the magnitude of this association was small, it was consistent over development. Erbeli et al (2020) reported similar findings in elementary children from grades 1 to 4, where annual change in math growth was (partially) accounted for by reading achievement. The reverse coupling, annual change in reading growth predicted by math achievement, was not found.…”
Section: Cross-domain Associations Between Reading and Mathematicssupporting
confidence: 58%
“…More recent work by Bailey et al (2020) draws further attention to the possible impact of the choice of analytical method on the cross-domain estimates obtained. In their study, the use of the traditional cross-lagged panel model yielded results similar to Duncan et al (2007); in contrast, use of more recently developed variations of this model-which account for potentially confounding unmeasured individual and environmental factors-yielded attenuated estimates of the cross-domain association between reading and mathematics, showing evidence of low (but larger) paths from reading to later math (see also, Erbeli et al, 2020). Intervention studies also add to the evidence for reciprocal cross-domain associations.…”
Section: Co-development Of Reading and Mathematicsmentioning
confidence: 92%
“…Several studies have shown that reading and mathematics are highly correlated (e.g., Koponen et al, 2007 ; Landerl and Moll, 2010 ; Codding et al, 2015 ; Balhinez and Shaul, 2019 ; Erbeli et al, 2020 ), and that comorbid disabilities occur far more often than isolated reading, and mathematics disabilities (e.g., Dirks et al, 2008 ; Willcutt et al, 2013 ; Koponen et al, 2018 ). Researchers have also argued that the observed covariation of reading and mathematics skills may be partly due to the fact that the development of both academic skills relies on similar cognitive processes (e.g., Koponen et al, 2007 , 2020 ; Zoccolotti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that interrelations among math and reading domains include socio-emotional dimensions, in addition to cognitive, neural, and genetic ones (e.g., Kovas et al, 2007;Pollack and Ashby, 2018;Vanbinst et al, 2020b). Indeed, in line with the notion that good reading skills may facilitate math skills, but not necessarily the reverse (Erbeli et al, 2021), how learners feel about reading may not just facilitate reading skills, but math skills as well.…”
Section: Socio-emotional Predictors Of Math Competence Are Within and Across Domainmentioning
confidence: 63%